Hubungan Neuropati Diabetikum dengan Kualitas Tidur Pada Pengidap DM Tipe 2 di Rumah Sakit Baladhika Husada Jember - Yurega Tri Adista Prahardini; Sasmiyanto Sasmiyanto; Ginanjar Sasmito Adi (Protein : Jurnal Ilmu Keperawatan dan Kebidanan., 2024)
Diabetic neuropathy is a complication of type 2 diabetes mellitus which is caused by lesions or nerve dysfunction in the lower extremities due to chronic hyperglycemia through peripheral and central mechanisms which can cause symptoms of tingling, numbness, numbness, pain, burning sensation, etc. sleep, thus affecting the sleep quality of people with type 2 diabetes mellitus. This aim is to analyze the relationship between diabetic neuropathy and sleep quality in people with type 2 diabetes mellitus at the Baladhika Husada Hospital, Jember. This research uses a correlation research design with a Cross-Sectional Study approach with a sample size of 43 respondents taken using the Pusposive Sampling technique. The statistical test results for diabetic neuropathy with sleep quality using the Spearman Rho test showed that the p value was 0.002 and r = 0.456, which means that diabetic neuropathy has a sufficient relationship with sleep quality. There is a negative relationship between diabetic neuropathy and the sleep quality of type 2 diabetes mellitus patients, so it can be said that increasing the severity of diabetic neuropathy will also affect the sleep quality of sufferers. The results of this research can be used as a guide for sufferers of type 2 diabetes mellitus with diabetic neuropathy to increase self-awareness in paying attention to lifestyle, maintaining diet, and routinely controlling medication in health services, in order to reduce the symptoms of diabetic neuropathy so as to improve the quality of sleep of sufferers.